Shared Hydrogen Atom Location and Chemical Composition in Picolinic Acid and Pyridoxal Hydrochloride Derivatives Determined by X-ray Crystallography - Crespi, Ayelen Florencia; Vega, Daniel Roberto; Sanchez, Veronica Muriel; Rodríguez Castellón, Enrique; Lazaro Martinez, Juan Manuel (American Chemical Society, 2022)
Fil: Crespi, Ayelen Florencia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Houssay. Instituto de Química y Metabolismo del Fármaco. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica. Instituto de Química y Metabolismo del Fármaco; Argentina